Beginning Teachers Improve With Attentive and Targeted Mentoring. (3rd April 2017) - Stanulis, Randi N.; Bell, Julie
Abstract: In the attentive, targeted mentoring framework, mentors shift their focus from helping beginning teachers merely survive the first year to empowering them to thrive and impact student learning .